The Role of Career Self-Efficacy (CSE) and Organizational Experience on Career Readiness: A Quantitative Study among Islamic Education Management - Salam, Ahmad Abdun; Pratiwi, Dwi Setyo (Jurnal Inovatif Manajemen Pendidikan Islam, 2026)
The Industrial Revolution 4.0 and Society 5.0 era demand that university graduates possess mature career readiness to combat the rising unemployment rate among graduates in Indonesia. This study analyzes the influence of Career Self-Efficacy (CSE) and Organizational Experience on the Career Readiness of Islamic Education Management students. Using an explanatory quantitative design, the research surveyed 146 students at UIN Syekh Wasil Kediri. The findings reveal that both CSE and organizational experience, both individually and simultaneously, significantly enhance career readiness. The study uniquely highlights how organizational involvement serves as a real-world laboratory that translates theoretical managerial concepts into practical readiness. Furthermore, the results indicate that these two factors account for 57.2% of the variance in student preparedness. This study contributes empirical evidence to career development literature specifically within the context of Islamic higher education management programs, offering a specialized perspective on how religious-based academic environments shape professional competence. Ultimately, strong self-belief and active organizational participation are essential for strengthening managerial skills and ensuring graduates are competitive in the modern workforce.